2015
DOI: 10.1007/s10919-015-0214-8
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Voices and Attractive Faces: The Contribution of Visual and Auditory Information to Integrated Person Impressions

Abstract: Faces and voices, in isolation, prompt consistent social evaluations. However, most human interactions involve both seeing and talking with another person. Our main goal was to investigate how facial and vocal information are combined to reach an integrated person impression. In Study 1, we asked participants to rate faces and voices separately for perceived trustworthiness, attractiveness, and dominance. Most previous studies relied on stimuli in which extra-vocal information (e.g., verbal content, prosody) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
75
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 62 publications
17
75
1
Order By: Relevance
“…Dominance of both faces and voices independently contributed to the impression formed when stimuli were presented multimodally. However, consistent with Rezlescu et al (2015) we found that voices had the larger effect on overall judgements.…”
Section: Overviewsupporting
confidence: 89%
See 4 more Smart Citations
“…Dominance of both faces and voices independently contributed to the impression formed when stimuli were presented multimodally. However, consistent with Rezlescu et al (2015) we found that voices had the larger effect on overall judgements.…”
Section: Overviewsupporting
confidence: 89%
“…Our approach therefore differs from those based on presentations of neutrally-worded reading passages or non-verbal vocalisations (e.g. vowels sounds), both of which are very commonly used techniques in this field (Berry, 1991;Rezlescu, et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations